Influence of Intraoral Temperature and Relative Humidity on the Dentin Bond Strength: An in Situ Study. Issue 2 (14th March 2014) - Saraiva, Letícia O.; Aguiar, Thaiane R.; Costa, Leonardo; Cavalcanti, Andrea N.; Giannini, Marcelo; Mathias, Paula
Abstract Statement of the Problem The effect of the intraoral environment during adhesive restorative procedures remains a concern, especially in the absence of rubber dam isolation. Objective To evaluate the temperature and relative humidity (RH) at anterior and posterior intraoral sites and their effects on the dentin bond strength of two‐step etch‐and‐rinse adhesive systems. Methods Sixty human molars were assigned to six groups according to the adhesive systems (Adper Single Bond Plus and One Step Plus) and intraoral sites (incisor and molar sites). The room condition was used as a control group. Dentin fragments were individually placed in custom‐made acetate trays and direct composite restorations were performed. The intraoral temperature and RH were recorded during adhesive procedures. Then, specimens were removed from the acetate trays and sectioned to obtain multiple beams for the microtensile bond strength test. In addition, the adhesive interface morphology was evaluated through scanning electron microscopy. Intraoral conditions were statistically analyzed by paired Students' t‐tests and the bond strength data by two‐way analysis of variance and Tukey test (α = 0.05). Results The posterior intraoral site showed a significant increase in the temperature and RH when compared with the anterior site. However, both intraoral sites revealed higher temperatures and RH than the room condition. In regards to the adhesive systems, the intraoral environment did not affect the bond strength, and the One Step Plus system showed the highest bond strength means. Conclusion Despite the fact that remarkable changes in the intraoral conditions were observed for both anterior and posterior sites, the intraoral environment was not able to compromise the immediate dentin bond strength. Clinical Significance Some conditions of intraoral temperature and relative humidity may not impair the dentin bond strength of two‐step etch‐and‐rinse adhesive systems. Thus, an adequate relative isolation seems to be a good alternative under the specific clinical conditions in which rubber dam isolation is either impossible or very difficult to perform.